Legal Protection for Public Shareholders on Forced Delisting of Securities by the Indonesian Stock Exchange - Darren Mayer Hadi Kusuma; Zahry Vandawati Chumaida; Agus Widyantoro (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study discusses the legal protection for public shareholders in the event of a forced delisting. This legal protection includes sanctions for public companies that fail to fulfill their legal obligation to repurchase all public shares. The novelty of this research lies in the fact that it not only examines the legal protection for investors that is normatively regulated by law but also delves into the legal responsibility for the losses suffered by investors as public shareholders when a public company fails to repurchase public shares following a forced delisting. The research employs a normative juridical method using a literature review of primary and secondary legal materials. The legal responsibility of a public company for investor losses is based on an unlawful act (onrechtmatige daad) committed by the public company for not fulfilling its legal obligation to repurchase all public shares as stipulated in OJK Circular Letter Number 13/SE.OJK.04/2023. The results show that investors have the right to legal protection in the event of a de-listing. These protections include the company's obligation to buy back all public shares, which is regulated in OJK Regulations. If the company does not fulfill this obligation, investors may suffer losses that can be remedied through administrative sanctions from OJK, such as warnings, fines, or revocation of business licenses. Companies that fail to fulfill their buyback obligations are considered to have committed an unlawful act and are liable for any losses suffered by investors. Therefore, listed companies need to be more compliant with capital market regulations to maintain investor confidence and market stability, as well as protect the rights of public shareholders.